The impact of valuable hierarchy of destructive behavior - Czernikiewicz, Andrzej; Baran, Tetiana (Current Problems of Psychiatry, 2013)
Prevention of criminal behavior should be focused on the prevention of crime by identifying superior value in human life, acceptance and love from parents to children, by creating the conditions for a worthy life. The aim of the study was to answer the question: "what is the role of possessed hierarchy of values in the etiology and severity of crime?” in a group of 100 men who were divided in two subgroups. The first group, the experimental group, included 50 men who had come in conflict with the law and were prisoned for more than 10 years. The second group, the control group, consisted of 50 men not entering into conflict with the law. The authors tested the hypothesis that the occurrence of criminal behavior may be related to difficulties in the hierarchy of values. In this study a special tool - Schelerian Values Scale (SWS) was used, adapted by Piotr Brzozowski. Empirical studies have shown a statistically significant difference between the results obtained by the punished individuals and the non-punished ones in terms of their hierarchy of values. At the same time, the presented results of studies are characterized by the relationship between the possessed hierarchy of values and the future criminal behavior.